A CRITICAL ANALYSIS OF TEACHER PROFESSIONAL COMPETENCIES IN PANCASILA EDUCATION LEARNING IN DEVELOPING STUDENTS' RESPONSIBLE CHARACTERS IN ELEMENTARY SCHOOLS - Riswanto; Ine Kusuma Aryani; Y. Suyitno; Subuh Anggoro (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to critically analyze the professional competence of teachers in Pancasila education in developing the character of responsibility in elementary school students. The qualitative research method with a case study design at Sidamulya 03 Public Elementary School. The research subjects included class teachers, students, and the principal. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using an interactive model including data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that the professional competence of teachers in Pancasila Education learning, which includes mastery of material, goal-based planning, development of creative and innovative teaching materials, continuous professionalism, and utilization of media and learning resources, plays a role in creating directed and meaningful learning. This has an impact on the development of students' character of responsibility, which is evident from the awareness of obligations as students, independence in the learning process, completing assignments well, not cheating, and punctuality in completing and submitting assignments. The implication is that strengthening teachers' professional competence is important in supporting character formation, especially responsibility, so that teachers and schools need to continue to develop contextual and character-oriented learning in a sustainable manner.